The influence of minimum dietary diversity on undernutrition among children aged 6-23 months in Ethiopia: a multilevel mixed-effect analysis based on 2019 Ethiopian mini demographic and health survey - Abdu Hailu Shibeshi; Zeytu Gashaw Asfaw (Frontiers Media S.A., 2024)
BackgroundUndernutrition persists as a critical issue in developing countries like Ethiopia due to poor feeding practices for infants and young children. The impact of dietary diversity on children's health in Ethiopia remains unclear, necessitating further investigation to develop effective prevention strategies.ObjectiveTo examine the association between minimum dietary diversity and undernutrition among children aged 6-23 months in Ethiopia.MethodsData from the 2019 Ethiopian Mini Demographic and Health Survey, including 1,501 women with children aged 6-23 months, were analyzed using STATA version 17 software. Child stunting, wasting, and underweight were assessed using Z-scores. Dietary diversity was measured using minimum dietary diversity. Multilevel logistic regression analysis determined associations, presenting results as crude odds ratios (COR) and adjusted odds ratios (AOR) with 95% confidence intervals (CI).ResultsOverall, 10.99% of children had adequate minimum dietary diversity, with Addis Ababa (44.57%) and Somalia (1.47%) showing the highest and lowest prevalences, respectively. The highest stunting prevalence was in the Amhara region (45.86%), while Addis Ababa had the lowest (9.78%). Wasting was lowest in Addis Ababa (1.09%) and highest in Tigray (17.07%). Underweight prevalence ranged from 2.17% in Addis Ababa to 33.33% in Tigray. Children with adequate minimum dietary diversity (MDD) had significantly lower odds of stunting (AOR = 0.68, 95% CI = 0.45, 0.96), underweight (AOR = 0.51, 95% CI = 0.27, 0.99), and wasting (AOR = 0.40, 95% CI = 0.17, 0.97) compared to those who had inadequate minimum dietary diversity (MDD).ConclusionThis study highlights the association between minimum dietary diversity and stunting, wasting, and underweight among Ethiopian children aged 6-23 months. Urgent nutrition-specific interventions are needed, particularly in regions with high undernutrition rates and low dietary diversity. Targeted interventions focusing on promoting diverse and nutritious diets for children, along with improving access to essential healthcare services, are imperative to mitigate the burden of undernutrition and ensure the well-being of Ethiopia's youngest population and reinforcing existing programs is crucial to address this public health issue effectively.